Evaluation of bioactive compounds from robust consortium microalgae species under actual flue gas exposure - Yahya, Liyana; Harun, Razif; Zainal, Afifi; Farahin, Abd Wahab (Elsevier, 2022)
The application of phototrophic microalgae for biological CO2 fixation has been regarded as a sustainable means to curb emissions, treat wastewater, and provide essential and valuable bioactive compounds that can serve multitudes industries, e.g., aquaculture, nutraceutical, and biofuel. This article highlights the utilization of microalgae consortium to enhance carbon fixation ability. Marine microalgae species were isolated and identified from their native condition of seawater discharge canals at the TNB Janamanjung Sdn. Bhd.s coal-fired power station. The experimental runs were performed with exposure of actual flue gas as a CO2 source from a live operating coal-fired power plant. The bioassays of protein and amino acids were conducted to the consortium to explore potential bio-products. The proximate analysis illustrated that the consortium content of protein (45), lipid (21), and carbohydrate (17) is comparable and more balanced from other types of mono species. Also, the essential amino acid content of 42 is encouragingly good and exceeds some other species and other sources. Premises and observations from various microalgae research works are collated and presented in a manner sufficient to highlight the essential roles of this tiny creature to become our mentor in providing some solutions to our worldly problems.